Enhancing Customer Loyalty at the Indonesian Classification Bureau through Satisfaction Creation with Service Innovation and Service Quality - Asfahani, Moh Basarudin; Wijaya, Chandra (GoAcademica Research & Publishing, 2024)
The focus of this study delves into the intricate dynamics among service innovation, service quality metrics, customer satisfaction levels, and the resultant loyalty patterns observed within the Indonesian Classification Bureau. The study investigates the direct impact of service innovation on service quality, customer satisfaction, and loyalty, while also exploring how service quality and satisfaction act as mediators in these relationships. Through rigorous regression and mediation analyses, the research reveals that service innovation enhances service quality but does not directly affect satisfaction or loyalty. Notably, improved service quality significantly correlates with higher levels of satisfaction and loyalty, with satisfaction playing a pivotal role in strengthening loyalty. These findings underscore the mediating roles of service quality and satisfaction in shaping the impact of service innovation on customer loyalty. The study advocates prioritizing initiatives to enhance service quality and implement effective loyalty programs. Furthermore, it recommends future investigations into specific types of service innovations and additional mediating factors that influence customer loyalty dynamics.